Morfoanatomia, composição química e atividade biológica do óleo essencial de espécies nativas de Lippia - Oliveira, Ariana Reis Messias Fernandes de (2014)
The aim of this study was to characterize the morphology, production, content, chemical composition and bioactive activity of essential oils of Lippia bromleyana, Lippia lasiocalycina, Lippia insignis and Lippia thymoides, endemic species of the Bahia semi-arid. The species were grown in the Experimental Station Horto Florestal State University of Feira de Santana (UEFS) in the city of Feira de Santana - Bahia. The essential oils are extracted from dry leaves and inflorescences, by hydrodistillation in Clevenger apparatus, and chemical composition was determined by GC/MS and GC/FID. Were carried out quantitative and qualitative morphological characterizations, in addition to agronomic characterization. The leaf anatomy, types and frequency of hair were observed in binocular microscope and electronic scanning light. The antioxidant activity was assessed by the ability of the substances present in the sample capture the free radical DPPH, using five concentrations of essential oils (2, 6, 10, 14 and 18 mg mL1) and the antifungal activity by mycelium growth in vitro testing five essential oil concentrations (0.25, 0.50, 0.75, 1.0 and 1.25 µL mL-1). In conditions where the study was conducted, it can be concluded that there are morphological differences between species in all traits, except only the number of flowers per inflorescence; there agronomic differences for all traits with L. lasiocalycina stood out in relation to the variable oil yield, while L. insignis and L. thymoides regarding the essential oil content; were identified six types of glandular trichomes one, two and tetracelular and three types of trichomes; the species L. bromleyana presents as differential anatomical absence of trichomes on the abaxial surface; L. thymoides has glandular trichomes with irregular contours on both sides, distinguishing it from other species; the frequency of trichomes on the abaxial surface is higher in species L. insignis and L. lasiocalycina, which are more anatomically similar; the major compounds found in the samples of essential oils of L. bromleyana, L. lasiocalycina, L. insignis and L. thymoides were piperitone oxide and limonene; E-ocimenona, myrcenone, myrcene, β-myrcene and ρ-cymene; thymol, myrcenone and E-ocimenona; and β-caryophyllene, germacrene D, respectively; L. insignis and L. bromleyana stood out in relation to the antioxidant and antifungal activity, respectively.